(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, the teacher’s readiness for professional activity, his personal and professional maturity, personal qualities, intellectual capabilities, social intelligence and its dependence on social and psychological factors are important in educating the intellectual young generation.